2003
DOI: 10.1348/135910703762879237
|View full text |Cite
|
Sign up to set email alerts
|

How sleep is related to fatigue

Abstract: The data further our understanding of the multifaceted nature of human fatigue and underline the greater importance of perceived sleep quality, compared to other sleep characteristics, in predicting fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 38 publications
8
58
0
6
Order By: Relevance
“…It has been found that cancer patients who are less active and have increased night awakenings report higher fatigue levels [3]. However, in a recent study fatigue has been shown to be associated with sleep quality but not with sleep latency [19]. An association between fatigue and the severity of pain has been confirmed in several research studies [8,21,27,30].…”
Section: Discussionmentioning
confidence: 98%
“…It has been found that cancer patients who are less active and have increased night awakenings report higher fatigue levels [3]. However, in a recent study fatigue has been shown to be associated with sleep quality but not with sleep latency [19]. An association between fatigue and the severity of pain has been confirmed in several research studies [8,21,27,30].…”
Section: Discussionmentioning
confidence: 98%
“…18 Fatigue is generally well correlated with sleep quality. 19 Previous involvement in a crash with injuries or fatalities was positively associated with moderate to severe impairments in sleep quality as assessed from the Pittsburgh Sleep Quality Index and negatively associated with answers from a simple query (''do you experience fatigue when driving? ''; a far less sensitive question).…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding corresponds to observed PSQI patterns in patients with CFS 35 and to the results of a population-based study, in which fatigue was predicted by sleep quality and psychological symptoms rather than by amount of sleep. 5 Both in populations reporting vital exhaustion and in populations reporting major stress or depression, a poorer quality of sleep has been reported by patients who show a reduction of slow wave sleep, which represents the stages of deep sleep and is thought to mark a restorative process. [36][37][38] From our descriptive study, we cannot infer causal relationships, nor can we disentangle temporal associations.…”
Section: Sleepmentioning
confidence: 99%
“…[5][6][7][8] Knowledge about the course of fatigue and related problems in a heterogeneous primary care population is scarce, however, because most longitudinal studies on fatigued populations have been performed in highly selected groups, such as patients with chronic fatigue syndrome (CFS), postviral fatigue, or cancer.…”
mentioning
confidence: 99%